1998
DOI: 10.1038/sj.onc.1201990
|View full text |Cite
|
Sign up to set email alerts
|

Translational induction of the c-myc oncogene via activation of the FRAP/TOR signalling pathway

Abstract: Previous studies on the regulation of c-myc have focused on the transcriptional control of this proto-oncogene. We have investigated the signalling pathways involved under circumstances in which there is a translational upregulation in the levels of c-myc protein. We have demonstrated an up to tenfold serum-dependent increase of c-myc protein levels in Epstein-Barr virus immortalized B-cell lines 2 ± 4 h after disruption of cellular aggregates, which is not accompanied by an equivalent increase in mRNA. Overal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
139
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 169 publications
(151 citation statements)
references
References 39 publications
(65 reference statements)
10
139
0
Order By: Relevance
“…The fact that the translation of cmyc is highly dependent on eIF4E is also inferred by its activation upon stimulation of the FRAP/mTOR pathway, which leads to the dissociation of the inhibitory proteins, 4E-BPs, from eIF4E (Mendez et al, 1997). This was recently con®rmed by a group who initially postulated the existence of the IRES in c-myc (West et al, 1998).…”
Section: Discussionmentioning
confidence: 94%
“…The fact that the translation of cmyc is highly dependent on eIF4E is also inferred by its activation upon stimulation of the FRAP/mTOR pathway, which leads to the dissociation of the inhibitory proteins, 4E-BPs, from eIF4E (Mendez et al, 1997). This was recently con®rmed by a group who initially postulated the existence of the IRES in c-myc (West et al, 1998).…”
Section: Discussionmentioning
confidence: 94%
“…Phosphoinositide 3-kinase (PI3K) and the downstream Akt/mammalian target of rapamycin (mTOR) pathway have essential roles in modulating cellular functions, activating molecules like ribosomal protein S6 kinase and the eukaryotic translation initiation factor 4E (eIF4E)-binding protein (4E-BP1), which contribute to the regulation of cell size, proliferation, and survival. 1,2 Therefore, the Akt/mTOR pathway is regarded as oncogenic and has the potential to be a therapeutic target. Several previous studies have demonstrated activation of the Akt/mTOR pathway and its contribution to cell survival and proliferation in SS cell lines [3][4][5][6] as well as the effects of the clinical application of therapeutic agents targeting mTOR in soft tissue sarcoma (STS).…”
Section: Introductionmentioning
confidence: 99%
“…It is not surprising therefore that the expression of c-myc is controlled at multiple levels including transcription, protein stability, RNA stability and translation (Eisenman, 2001). The translational regulation of c-myc is complex and the synthesis of this protein can be initiated via two mechanisms (Nanbru et al, 1997;Stoneley et al, 1998;West et al, 1998). c-myc mRNA translation initiation can occur by cap-dependent scanning, which requires the binding of the multimeric complex eIF4F (which is comprised of the cap-binding protein eIF4E, the DEAD-box helicase eIF4A and the scaffold protein eIF4G) to the 7-methyl-G cap structure of the mRNA, followed by recruitment of the 40S ribosomal subunit, and scanning to the first AUG codon, which is in an adequate context (Gray and Wickens, 1998).…”
Section: Introductionmentioning
confidence: 99%